IoT-SUPPORTED AUTOMATED SYSTEM FOR WATER QUALITY MONITORING IN AQUAPONIC SYSTEMS (2024)
The national program for science, technology and innovation in agricultural sciences proposes the implementation of efficient and sustainable innovation systems alternatives to traditional fish farming practices. In aquaponics, it has not been possible to implement automated water quality control monitoring systems, due to the high costs and the misinformation that is created around new technologies, such as the Internet of Things (IoT). Thus, this work had the purpose of implementing a prototype supported by IoT and energized by photovoltaic energy for the monitoring of dissolved oxygen (DO), temperature (T), pH, electrical conductivity (EC) and salinity in the commissioning of a medium-scale aquaponic system in the municipality of Lengupa-Boyacá. The hardware architecture was carried out using an Arduino card, an electronic board based on the Atmega2560 microprocessor and a power source was supported by a photovoltaic solar panel. The results show that it is possible to implement prototypes supported by the IoT and powered by photovoltaics for the monitoring of DO, T, pH, EC and salinity in aquaponic systems. The collection and visualization of data in real time could contribute to timely decision making.